Collaborative Social Service Model in Handling People with Social Problems in West Java - Admiral Nelson Aritonang; Suharma Suharma; Versanudin Hekmatyar (International Seminar on Social Work Update, 2023)
The objective of this study is to analyze the effectiveness and efficiency of collaborative social service models in dealing with people with social problems in West Java. The research was conducted using a sequential explanatory design that combined quantitative and qualitative data. The sample of the study consisted of social service providers and people with social problems who had used the collaborative social service model. The data were collected through interviews, questionnaires, and documentation studies. The data were then analyzed using descriptive statistics, content analysis, and thematic analysis. The findings showed that the collaborative social service model in West Java had improved the quality of social services in terms of speed, accuracy, and completeness. The collaboration between social service providers had increased the effectiveness and efficiency of services. The establishment of the Integrated Social Service Center (PLST) had also provided a one-stop service for people with social problems. However, community participation in the model still needed improvement to ensure the sustainability of the services. In conclusion, the collaborative social service model in West Java has provided a comprehensive and integrated approach to handling people with social problems. The model has improved the quality of social services provided by increasing collaboration and establishing a one-stop service center. However, community participation is crucial to ensure the sustainability of the services.